Evaluasi Aplikasi Sampurasun Purwakarta dalam Penerapan E-Government di Bidang Pariwisata Kabupaten Purwakarta - Wiwi Trifina Syalawalianti; Haura Atthahara; Ani Nurdiani Azizah (Peneliti.net, 2021)
E-government in the Central or Regional government is one of the uses or utilization of information and communication technology in welcoming the industrial revolution 4.0. The Purwakarta Regency Government through the Tourism and Culture Sector launched a digital-based application called the Sampurasun Purwakarta application which aims to provide facilities or services to facilitate all information in the tourism sector for tourists while in Purwakarta. This study uses qualitative methods by collecting data through literature study, observation and interviews. The Sampurasun Purwakarta application has been implemented for approximately 3 years so it is necessary to evaluate policies using evaluation theory according to William & Dun which has six indicators including effectiveness, efficiency, adequacy, equity, responsiveness and accuracy. With the results of research showing that the application of the Sampurasun Purwakarta application in the tourism sector has provided new changes and conveniences in the tourism sector, although there is still a need for interactive development and improvement, feedback and utilization of the application.